Resistência à inovação: uma análise da influência das barreiras cognitivas e emocionais no comportamento do consumidor - Santos, Alexandre Alves dos (2022)
Efforts to understand the mechanisms that lead consumers to adopt or reject innovative products or services are important to prevent investments in these innovations from generating revenue. The number of new products and services that fail to be launched on the market is relatively high and those that do not fail are not readily adopted by most consumers, signaling that resistance is a common consumer response to innovation. Currently, the existing literature presents two types of resistance: passive resistance to innovation, which precedes active resistance to innovation, both of a cognitive nature, being disregarded in most studies the emotional aspects. Thus, this master's thesis addresses both functional and psychological barriers (cognitive in nature) and emotional barriers of resistance to innovation. In this context, the main objective of this study is to understand the influence of functional, psychological and emotional barriers of the consumer on the resistance to the use of digital banking services. This research is quantitative in nature and primary data were collected through a self-filled online questionnaire. A final sample of 202 adult Brazilians, with and without experience in the use of digital banking services, allowed the test of research hypotheses through structural equation modeling (PLS-SEM). Understanding the factors that lead consumers to resist innovations is essential both academically and professionally. The main theoretical contribution of this work is to identify the greater influence of emotional barriers, compared to functional barriers, on the resistance to innovation in the field of digital banking services. The main models of resistance to innovation existing place greater emphasis precisely on functional aspects, but could benefit from the incorporation of emotional aspects. The results also provide managerial implications, by favoring the design of communication programs capable of reducing the chances of failure of an innovation. Possibilities for future research are also discussed.